PENGEMBANGAN USAHA PERIKANAN SKALA KECIL MELALUI PENENTUAN DAERAH PENANGKAPAN IKAN POTENSIAL DAN MANAJEMEN USAHA - Waileruny, Welem; Matrutty, Delly D P; Kesaulya, T; Nanlohy, Alberth Ch; Tuapetel, Frisland (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Determination of fishing ground by small-scale fisheries is still based on experience passed down from generation to generation. Fishermen do not yet have the knowledge and technology to make it easier for them to determine a good fishing ground, so it is inefficient in terms of time, cost and effort. In addition, business management that is not running properly has resulted in the business being run not developing. This training aims to increase fishermen's knowledge about determining potential fishing grounds, specifically for demersal fish species and management of small-scale fisheries. The training activities were carried out in Hukurila Village, South Leitimur District, Ambon City. The method of implementation is presentation of materials, discussions and than training in making bookkeeping simple. Participants were 31 fishers who were involved in this activity. Fishers felt that the material they received was very useful because it made it easier for them to determine demersal fishing areas that had important economic value. In addition, business bookkeeping through training has helped them manage the finances of the business they are running.